UNVEILING SYNERGIES: EXPLORING THE INTERPLAY OF HEALTH DIMENSIONS IN A HOLISTIC HEALTHCARE LANDSCAPE - AHMED MOHSEN ALI AL ISHAG, Mohammed Mohsen Ali Al Ishaq, Jafar Mohammed A Al Ishaq, Meshal Mohsen Ali Al Ishaq, Rubayan Yahya Rubayan AL Ishaq, Ali Muhsin Ali Al Ishaq, Mohammed Salem A Al Kubaybah (Chelonian Research Foundation, 2023)
This article explains the relationship between different health angles, including public health, health surveillance, clean health insurance, and empirical work. By combining existing inquiries about and developing patterns, this audit clarifies challenges, issues, and openings to make more advantageous persistent co-sharing. At a time checked by phenomenal innovative advances and advancing therapeutic standards, understanding the energetic interaction of this measurement of healthcare has become critical. A blend of existing investigations not only gives an understanding of current issues, such as integration of data and moral contemplations within the utilization of healthcare data but also highlights the openings that innovation propels to integrationlooking into advocates of collaborative, collaborative innovation to shut incongruities in treatment, tending to the need for guidelines and moral contemplations. The extreme objective is to form a more coordinated and worldwide healthcare framework vital for human health and societal healthcare, laying the establishment for widespread healthcare and patients.